Disease Stage-Specific Pathogenicity of CD138 (Syndecan 1)-Expressing T Cells in Systemic Lupus Erythematosus - Liu, Lunhua; Takeda, Kazuyo; Akkoyunlu, Mustafa (Frontiers in Immunology, 2020)
CD138 (syndecan 1), a member of the heparan-sulfate proteoglycan family, regulates diverse biological responses by interacting with chemokines, cytokines, growth factors and adhesion molecules. Expression of CD138 has been detected on T cells from both healthy and sick mice mimicking systemic lupus erythematosus (SLE) disease. However, the characteristics and the role of CD138+ T cells in SLE pathogenesis remain largely unknown. We analyzed the lupus-prone MRL/Lpr mice and the control MRL/MpJ strain as well as the common laboratory strains Balb/c, and C57BL/6 for CD138-expression and found that only the MRL/Lpr strain harbored TCRβ+CD138+ cells in various organs. The frequency of TCRβ+CD138+ cells progressively expanded in MRL/Lpr mice with age and correlated with disease severity. Majority of the TCRβ+CD138+ cells were CD4 and CD8 double-negative and 20% were CD4. At least a portion of TCRβ+CD138+ cells originated from CD4+ cells because substantial number of CD4+TCRβ+CD138- cells expressed CD138 after in vitro cultivation. Compared to TCRβ+CD138- cells, TCRβ+CD138+ cells exhibited central memory (Tcm) phenotype with reduced ability to proliferate and produce the cytokines IFNγ and IL-17. When co-cultured with B cells, the ability of TCRβ+CD138+ cells to promote plasma cell formation and autoreactive antibody production was dependent on the presence of autoantigen, CD4 co-receptor expression and cell-to-cell contact. Surprisingly, adoptively transferred TCRβ+CD138+ T cells slowed down disease progression in young recipient MRL/Lpr mice but had the opposite effect when DNA was co-administered with TCRβ+CD138+ T cells or when TCRβ+CD138+ cells were transferred to older MRL/Lpr mice with established disease. Thus, CD138-expressing T cells with Tcm phenotype enhance disease progression in SLE by rapidly activating autoreactive B cells when self-antigens are exposed to the immune system.